2009
DOI: 10.1002/app.31154
|View full text |Cite
|
Sign up to set email alerts
|

Fire‐retardant copolymer of acrylonitrile with O,O‐diethyl‐O‐allyl thiophosphate

Abstract: A novel halogen-free flame retardant, O,Odiethyl-O-allyl thiophosphate (DATP), which simultaneously contained phosphorus and sulfur, was synthesized through a simple method. The structure of DATP was characterized by Fourier transform infrared spectroscopy, 1 H-NMR, and mass spectroscopy. The flame-retardant copolymer was obtained by the free-radical copolymerization of DATP with acrylonitrile. The flammability and thermal degradation characteristics of the copolymer were assayed by limiting oxygen index measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…After phosphorylation, new absorption bands at 1160 cm −1 and 938 cm −1 were observed due to the presence of PO and POC groups . The results confirm that Am‐PAN‐ g ‐GMA was successfully reacted with phosphorous acid to obtain flame‐retardant PAN fabric.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…After phosphorylation, new absorption bands at 1160 cm −1 and 938 cm −1 were observed due to the presence of PO and POC groups . The results confirm that Am‐PAN‐ g ‐GMA was successfully reacted with phosphorous acid to obtain flame‐retardant PAN fabric.…”
Section: Resultssupporting
confidence: 59%
“…It was found that phosphorus acid decomposed from the copolymer could catalyze the cyclization of the copolymers to form char; however, the greater the steric effect of the comonomer, the more difficult is the cyclization of the copolymer. Ren et al . synthesized the copolymer acrylonitrile– O,O ‐diethyl‐ O ‐allylthiophosphate and found the fire retardancy and the amount of char residue of the copolymer are increased.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is renewed effort to investigate and develop new classes of flame resistant acrylic fibers with nontoxic and smokeless. The phosphorus‐containing compounds and sulfur‐containing compounds then were introduced to acrylic fibers by copolymerization, blending, post‐treating and many other methods . Although, the phosphorus flame retardants are effective to improve the flame resistance of the acrylic fibers, the commercial use of the phosphorus flame retardants for acrylic fibers are few reported yet for many reasons, such as poor thermal resistance, complex architecture and high additive amount to acquire the good flame retardant property.…”
Section: Introductionmentioning
confidence: 99%
“…Modacrylic fiber is the only industrialized copolymerization fire retardant PAN fiber; nevertheless, modacrylic fiber is greatly restricted because the fiber can release toxic hydrogen halide and amounts of smoke during combustion. Halogen‐free comonomers can be used to copolymerize with acrylonitrile to improve the fire retardant performance of acrylonitrile polymers. However, the copolymerization flame retardant method also has some defects, such as higher synthetic cost, difficulty of copolymerization with acrylonitrile, and poor spinnability of the fire retardant acrylonitrile copolymers .…”
Section: Introductionmentioning
confidence: 99%
“…Halogen‐free comonomers can be used to copolymerize with acrylonitrile to improve the fire retardant performance of acrylonitrile polymers. However, the copolymerization flame retardant method also has some defects, such as higher synthetic cost, difficulty of copolymerization with acrylonitrile, and poor spinnability of the fire retardant acrylonitrile copolymers . Plasma grafting is a relative complex and difficult technique to operate, which limits the application of this technique to some extent.…”
Section: Introductionmentioning
confidence: 99%